Cognate Plants: A Renewed Concept for Species with Common Uses and Taxonomic Similarities - Marcus Vinicius de Athaydes Liesenfeld (Ethnobiology Letters, 2025)
The article introduces the cognate plant concept, presenting its novel application within an ethnobiological context. These are taxonomically or functionally analogous plant in-groups that remain overlooked and undervalued in public perception. In order to support the term definition, several examples of related plants are discussed, such as those used in the production of piaçaba, cipó-titica, and tauari wood, as well as the açaí case. In each example, the importance of correctly identifying the species is emphasized to warn against unsustainable extraction practices. Moreover, inaccurate consumer perception of the product offered can overshadow conservation problems with one or more of the cognate species that are the source of the raw material. In the açaí case, the introduction of Euterpe oleracea beyond its native range, alongside the native Acre açaí (Euterpe precatoria), raises concerns about socio-environmental impacts and the potential transition from extractive systems to monocultures. Although examples cited are from Brazil and the Amazon, the applicability of this concept extends universally. Therefore, incorporating the plant cognate concept into research, policy, and community practices offers a more realistic approach to biodiversity conservation while supporting cultural traditions and sustainable resource management.